A FOCUS ON THE LITERATURE REVIEW OF NANOREFRIGERANTS - Dalkilic, Ahmet Selim; Aktas, Melih; Celen, Ali; Cebi, Alican; Mahian, Omid; Wongwises, Somchai (AMER SOC MECHANICAL ENGINEERS, 2014)
The heat transfer performance of various thermal devices can be augmented by active and passive techniques. One of the passive techniques is the addition of nanoparticles had the size of 1 and 100 nanometers to the common heat transfer so that the thermal transport properties of the prepared suspension called nanofluid will be enhanced compared to the base fluid. Nanorefrigerants as a special type of nanofluids which are mixtures of nanoparticles and refrigerants have a wide range of applications in diverse fields such as refrigeration, air conditioning systems and heat pumps. In this study, the missing points on this new method are also indicated regarding the lack of studies on the determination of physical properties of nanorefrigerants and the flow of nanoparticles.
Keywords: HEAT-TRANSFER CHARACTERISTICS; THERMAL-CONDUCTIVITY; TIO2 NANOPARTICLES; REFRIGERANT; PERFORMANCE; NANOFLUIDS; VISCOSITY; FLOW; ENHANCEMENT; MIGRATION; Engineering